Strategi Humas PT. Suryacipta Swadaya Untuk Meningkatkan dan Mempertahankan Citra Terhadap Warga Desa Kutanegara–Karawang Timur - Riswandi, Riswandi; Alfirahmi, Alfirahmi (LUGAS Jurnal Komunikasi, 2023)
The development of industry in Indonesia is very rapid, including the Suryacipta industrial area which is located in the East Karawang-West Java area. Area expansion has always been on the company's agenda in business development efforts, but it have the possibility of causing environmental problems that will affect the demographics of the people around the area. Therefore, the company must try to improve its image by carrying out environmental and other social responsibility programs. The purpose of this study was to determine the public relations strategy of PT. Suryacipta Swadaya in increase and maintaining its image, the obstacles faced, and solutions to solve it. In this study, researchers used a qualitative approach with qualitative descriptive methods, data collection techniques in the form of observation and interviews. The results of the study that PT. Suryacipta Swadaya in general still has a positive image of the people of Kutanegara village by carrying out several public relations strategies that refer to the public relations strategy according to Anwar Arifin. But behind it still leaves environmental and social problems that do not appear on the surface which can potentially become conflicts in the community and can disrupt the stability of industrial areas. Even though, a positive image can be maintained because the majority of people get the economic benefits of the existence of the industrial area. The suggestions given in this research for PT. Suryacipta Swadaya, the public relations officer must actively conduct observations and direct approaches to the affected lower-level communities, so that very basic problems can be handled more quickly and precisely